2019
DOI: 10.1177/1550147719861020
|View full text |Cite
|
Sign up to set email alerts
|

Damage and fractal evolution trends of sandstones under constant-amplitude and tiered cyclic loading and unloading based on acoustic emission

Abstract: It is of significance to study the damage and destruction of rock under cyclic loading in geotechnical engineering. We determined the trends in damage evolution of sandstone under constant-amplitude and tiered cyclic loading and unloading under uniaxial compression. The results of the study show that (1) the variation of acoustic-emission events was consistent with the stress curves and 89% of all acoustic-emission events occurred during the cycling stages. The observed Kaiser effect was more notable in tiered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 35 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Another type of time-dependent inelastic deformation is known as creep deformation, in which the material constantly deforms under the application of a constant and persistent external load, irrespective of the stress levels [161,156]. Lastly, damage strain can occur which can initiate microcracks and lead to the failure of rocks [162,163]. Few rocks also show anisotropic elastic deformation which needs to be accounted for effectively using appropriate constitutive formulations [164,165,166].…”
Section: Geomechanical Constitutive Modelsmentioning
confidence: 99%
“…Another type of time-dependent inelastic deformation is known as creep deformation, in which the material constantly deforms under the application of a constant and persistent external load, irrespective of the stress levels [161,156]. Lastly, damage strain can occur which can initiate microcracks and lead to the failure of rocks [162,163]. Few rocks also show anisotropic elastic deformation which needs to be accounted for effectively using appropriate constitutive formulations [164,165,166].…”
Section: Geomechanical Constitutive Modelsmentioning
confidence: 99%
“…Meng et al [ 10 ] used the MTS815 rock mechanics test system to carry out triaxial cyclic loading and unloading tests on limestone with different surrounding rocks, and studied the strength, dilatancy deformation and damage mechanical properties of rock during cyclic loading and unloading. In addition, many scholars conducted detailed research on the damage and failure of coal and rock mass during cyclic loading and unloading from the perspectives of plastic deformation [ 11 , 12 ], energy dissipation [ 13 , 14 ] and acoustic emission characteristics [ 15 , 16 ] of coal and rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…M. W. Zhang et al [36,37] believed that the Felicity effect of rock in the elastic phase of rock deformation decreases as the unloading rate increases. D. X. Liang et al [38,39] analyzed the Kaiser effect under cyclic loading and unloading on rocks, and found that the greater the rock hardness is, the earlier the Kaiser stress point appears. The Kaiser effect is more obvious under stepped cyclic loading.…”
Section: Introductionmentioning
confidence: 99%